Perceived effectiveness and recommendations from a childbirth quality assurance and improvement programme in India’s private sector: a qualitative evaluation using the RE-AIM framework - Katherine Semrau; Meghna Desai; Lauren Spigel; Somesh Kumar; Megan Marx Delaney; Lauren Bobanski; Suranjeen Pallipamula; Natalie Henrich; Tapas Sadasivan Nair; Hema Divakar; Rajat Chabba; Shweta Jindal; et al. (BMJ Public Health, 2025)
Introduction Previous studies have revealed inconsistent quality of care in India’s private sector, where nearly one in three facility births take place. Manyata is a quality assurance and improvement programme launched in 2016 by the Federation of Obstetrics and Gynaecological Societies of India (FOGSI) that provides training, mentorship and accreditation to private maternity facilities. We aimed to understand participants’ motivations for joining or not joining, the perceived value of Manyata and recommendations for sustainment and scale.Methods We aimed to sample 238 Manyata participants for semi-structured, in-depth interviews between February and July 2021. Participants included facility owners, nurses, FOGSI quality assessors, programme implementers and Manyata leaders. Data were coded and analysed using a deductive and inductive process. Codes were mapped to the Reach, Effectiveness, Adoption, Implementation and Maintenance (RE-AIM) framework, which we expanded to include scale.Results We interviewed 185 programme participants. Maternity facility owners joined Manyata due to its affiliation with FOGSI, encouragement from peers and the desire to standardise care and train their staff. Barriers to joining included cost, unclear value and little motivation to improve practice. Participants most valued Manyata for improving staff competency, quality of care, standardised care processes and staff satisfaction. Participants felt that continuous training, mentorship and quality assurance would be necessary to maintain Manyata over time, and Manyata could and should be scaled across India and to other countries.Conclusion Strategies for engaging with the private sector should include building strategic partnerships and messaging a value proposition that emphasises training, standardised care processes and improved quality of care. A blended virtual and in-person model may be leveraged for ongoing training and quality assurance and to scale across contexts. Our evaluation of Manyata distills tangible lessons that policymakers, professional societies and public health practitioners can use to bridge the quality gap in their own private-sector maternity systems.